2020
DOI: 10.1002/cam4.3618
|View full text |Cite|
|
Sign up to set email alerts
|

Trifluridine/tipiracil plus bevacizumab as a first‐line treatment for elderly patients with metastatic colorectal cancer (KSCC1602): A multicenter phase II trial

Abstract: Background A previous Phase I/II study demonstrated that TAS‐102 (trifluridine/tipiracil [FTD/TPI]) plus bevacizumab (Bev) has encouraging efficacy and controllable safety for patients with previously treated metastatic colorectal cancer. Therefore, we designed for assessing the efficacy and safety of FTD/TPI plus Bev in elderly patients with previously untreated metastatic colorectal cancer. Methods This is a multicenter, single‐arm Phase II study included patients ≥70… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…In the Asian Phase III study, patients aged ≥65 years even seem to obtain a greater benefit than those <65 years [24]. A recent Phase II study in untreated patients aged ≥70 years demonstrated the safety of FTD/TPI in combination with bevacizumab (Bev) both in fit and vulnerable subjects, despite increased toxicity induced by Bev [25].…”
Section: Resultsmentioning
confidence: 99%
“…In the Asian Phase III study, patients aged ≥65 years even seem to obtain a greater benefit than those <65 years [24]. A recent Phase II study in untreated patients aged ≥70 years demonstrated the safety of FTD/TPI in combination with bevacizumab (Bev) both in fit and vulnerable subjects, despite increased toxicity induced by Bev [25].…”
Section: Resultsmentioning
confidence: 99%
“…Recent data from the KSCC1602 study showed that bevacizumab combined with TAS-102 was an effective and well-tolerated regimen for elderly patients with untreated mCRC over 70 years of age. The median PFS was 9.4 months, the median OS was 22.4 months, and the ORR was 40.5% ( 36 ). This means that this treatment plan is expected to become one of the standard treatment options for metastatic colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In the setting of advanced unresectable or metastatic GC, chemotherapy should be offered to patients with adequate performance status and organ function, as it improves QoL and survival outcomes over the best supportive care (BSC) alone [ 88 , 89 ]. Moreover, combination chemotherapy yields a survival advantage compared to single-agent regimens and is to be preferred over monotherapy in patients fit for combinatorial approaches [ 90 ].…”
Section: Nutritional Support Strategiesmentioning
confidence: 99%